2014
DOI: 10.1038/ncomms6183
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-dimensionality-induced helimagnetism in iron nanoislands

Abstract: Low-dimensionality in magnetic materials often leads to noncollinear magnetic order, such as a helical spin order and skyrmions, which have received much attention because of envisioned applications in spin transport and in future data storage. Up to now, however, the real-space observation of the noncollinear magnetic order has been limited mostly to systems involving a strong spin-orbit interaction. Here we report a noncollinear magnetic order in individual nanostructures of a prototypical magnetic material,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 34 publications
1
38
0
2
Order By: Relevance
“…Not only the sign of the asymmetry is preserved, but also the monotonous variation as a function of θ Co . The physical concept reported here can be of general application in a large variety of magnetic substrates with noncollinear ground states: 2 AL Fe/Cu(111) [26], 2 AL Mn/W(110) [22], 1 AL Mn/W(100) [27], 1 AL Mn/Ag(111) [21], 2 AL Fe/W(110) [28], 1 AL Fe/Ir(111) [29], and NiMn(001) [30]. This work opens a way to study not only the coupling of adatoms to those substrates, but also the possible magnetic interactions among atoms in artificial structures built by atomic manipulation.…”
Section: (D) and 2(e) Provided That P T = 0 And Aφ/w < 90mentioning
confidence: 99%
“…Not only the sign of the asymmetry is preserved, but also the monotonous variation as a function of θ Co . The physical concept reported here can be of general application in a large variety of magnetic substrates with noncollinear ground states: 2 AL Fe/Cu(111) [26], 2 AL Mn/W(110) [22], 1 AL Mn/W(100) [27], 1 AL Mn/Ag(111) [21], 2 AL Fe/W(110) [28], 1 AL Fe/Ir(111) [29], and NiMn(001) [30]. This work opens a way to study not only the coupling of adatoms to those substrates, but also the possible magnetic interactions among atoms in artificial structures built by atomic manipulation.…”
Section: (D) and 2(e) Provided That P T = 0 And Aφ/w < 90mentioning
confidence: 99%
“…Spin-polarized scanning tunneling microscopy and spectroscopy (spin-STM/S) is a magnetic imaging technique with an ultimate lateral resolution on the atomic scale [14], which is suitable for probing magnetism in ferromagnetic nanostructures [57] and in antiferromagnets [810]. Figure 1a schematically describes electron tunneling in spin-STM.…”
Section: Introductionmentioning
confidence: 99%
“…Here we focus on biatomic-layer-high (BLH) Co, Fe, and Fe-decorated Co (Fe|Co) islands on Cu(111) [7, 1820]. Figure 2a schematically illustrates the sample preparation procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of 2 ML Fe islands on Cu(111), it has been shown that a martensitic phase transition between ferromagnetic body-centered cubic(bcc) and antiferromagnetic facecentered cubic (fcc) phases is induced upon application of high electric fields. Herein, the coexistence of two different crystallographic phases and the complex magnetic order are closely interwoven 3,6 . Considering the interatomic distances between nearest neighbors d nn and the resulting lattice mismatch, a Ni(111) surface where d nn = 248 pm should be an ideal candidate to promote the coexistence of Fe fcc (d nn = 253 pm) and bcc (d nn = 247 pm) films.…”
mentioning
confidence: 99%